ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEPATUHAN PAJAK WAJIB PAJAK BADAN PADA PERUSAHAAN INDUSTRI MANUFAKTUR DI DAERAH ISTIMEWA YOGYAKARTA - Didik Irawan; Alia Ariesanti (Universitas Ahmad Dahlan, 2015)
The purpose of the research is to analyze the behavior of tax compliance of corporate taxpayers, particularly large industrial manufacturing company that exists through out Daerah Istimewa Yogyakarta, represented by professional tax who work at the company. The results of this study indicate that: (1) the strength or weakness of a professional tax attitude does not affect the level of tax compliance in a corporate entity, (2) subjective norm has no effect on the level of corporate tax compliance, (3) strong or weak moral obligation of professional tax does not affect the level of tax compliance in a corporate entity, (4) the strength or weakness of a professional tax intention to behave not affect the level of tax compliance in a corporate entity, (5) the company 's financial condition does not affect the level of corporate tax compliance, (6) large or a small facility of company where professional tax work does not affect the level of tax compliance from a corporate entity, (7) organizational climate where professional tax work affects the level of tax compliance from a corporate entity. This study also represents that professional tax do not greatly affect the level of tax compliance in the corporate taxpayers large manufacturing company in Daerah Istimewa Yogyakarta.